Analysis of the Implementation of Financial Accounting Standards Statement (PSAK) 117 Concerning Insurance Contracts for Social Security Funds Managed by Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan - Aryo Wibisono; Ludovicus Sensi Wondabio (Eduvest - Journal of Universal Studies, 2026)
This research analyzes the implementation of Financial Accounting Standards Statement (PSAK) 117 on insurance contracts within the Social Security Fund (DJS) managed by BPJS Kesehatan, focusing on the conceptual and technical challenges that arise from the fundamental differences between social insurance schemes and the commercial insurance model. Using a qualitative approach grounded in regulatory review, academic literature, and BPJS Kesehatan’s technical documents, this research examines twelve critical issues of PSAK 117 relevant to the National Health Insurance (JKN)program, including the definition of insurance contracts, contract boundaries, measurement models, risk adjustment, and the relevance of the Contractual Service Margin (CSM). The analysis shows that the legal relationship between participants and BPJS Kesehatan meets the contractual criteria stipulated in PSAK 117; however, its practical application requires adjustments to align with the characteristics of social insurance. Key challenges include the need for more granular actuarial data, the establishment of fulfillment cash flows that reflect collective population risk, and the misalignment of the CSM concept with a program that is not designed to generate profit. This study concludes that the implementation of PSAK 117 enhances transparency and accountability in financial reporting while simultaneously demanding stronger institutional capacity within BPJS Kesehatan and the development of tailored accounting guidelines for social security entities to ensure alignment between accounting standards, the mandate of the National Social Security System (SJSN), and the long-term sustainability of the DJS Kesehatan program.